AFRICAN FEMINIST PHILOSOPHY: THE CREATION OF A MORAL CONFUSION? - Gaie, Joseph B.R. (European Scientific Journal, ESJ, 2013)
﻿The uninitiated or novice might easily believe that Feminist Philosophy is something easy to define. Once we have defined Feminist Philosophy we can easily suggest that African Feminist Philosophy is Feminist Philosophy that belongs to Africa or Africans or something to that effect—such as philosophising about feminist ideas in and for African women. My thesis is that the concept of African Feminist Philosophy is nothing like a Western type conception of feminism. The suggestion that African Feminism is like Western Feminism amounts to moral confusion. I will use the Setswana traditional idea of woman to demonstrate this argument. Even though women are oppressed in the world, their idea of oppression does not and may not necessarily be the same. The Western type of women liberation might not necessarily be what African women want. It is therefore a moral imperative to define and chart a clear and peculiar path for African Feminism and feminism in general will have to accept this as part of the universal liberation movement for women.